GLMM and GLMMTree for Modelling Poverty in Indonesia - Suseno Bayu; Khairil Anwar Notodiputro; Bagus Sartono (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
GLMMTree is a tree-based algorithm that can detect interaction and find subgroups in the GLMM to improve fixed effect estimation. This study uses GLMMTree for the actual data applications of poverty in Indonesia and confirms that the GLMMTree algorithm method has better precision than GLMM. The significant predictors that affect poverty in Indonesia are the unemployment rate and the GRDP at a constant price. GLMMTree algorithm enriches the analysis by finding subgroups of provinces with electricity lighting access and clean drinking water sources variables.